Afanas'ev, Ivan Mikhailovich (philologist)
Chernobyl as a worldview in contemporary Belarusian literature; why Belarusian literature lacks any worthwhile work about Chernobyl; about existential questions raised by Chernobyl and the degree to which they are understood by Belarus society.